2019
DOI: 10.21037/jtd.2018.11.56
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery (ERAS) programs for esophagectomy

Abstract: A perioperative treatment protocol, enhanced recovery after surgery (ERAS) focuses on accelerating patient recovery. Previous studies confirmed that ERAS decreases surgical trauma and the stress response, which improved outcomes including reduced length of hospital stay (LOS) and decreased postoperative morbidity. While ERAS protocols have been successfully implemented in a variety of surgical disciplines (colorectal, bariatric, orthopedic, and gynecologic surgery), its use in esophageal surgery is still limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…In the postoperative phase, patients were treated by principles of a “fast track” protocol with extubation as soon as possible, early enteral nutrition and mobilization at the earliest convenience [ 39 ]. Usually, patients were monitored at the ICU after abdomino-thoracic esophagectomy for at least until POD 1 and—if cardiac and respiratory functions were stable—discharged from the ICU.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the postoperative phase, patients were treated by principles of a “fast track” protocol with extubation as soon as possible, early enteral nutrition and mobilization at the earliest convenience [ 39 ]. Usually, patients were monitored at the ICU after abdomino-thoracic esophagectomy for at least until POD 1 and—if cardiac and respiratory functions were stable—discharged from the ICU.…”
Section: Methodsmentioning
confidence: 99%
“…In the postoperative phase, patients were treated by principles of a "fast track" protocol with extubation as soon as possible, early enteral nutrition and mobilization at the earliest convenience [39].…”
Section: Surgerymentioning
confidence: 99%
“…If the results of that study showed patent anastomosis, low residual soft food intake was allowed. Patients could be discharged on postoperative day 8 if they met the discharge criteria (6,11).…”
Section: Materials and Methods Materials And Methodsmentioning
confidence: 99%
“…ERAS is a multidisciplinary approach that aims to promote early postoperative recovery, reduced surgical stress response and organ dysfunction, decreased postoperative complications, reduced length of hospital stay and hospitalization cost, and improved long-term survival (3)(4)(5). ERAS has been successfully applied in many fields of surgery, including gastric and esophageal surgery (6)(7)(8). Although the safety and efficacy of the ERAS protocol in UGI surgery has been reported in numerous studies, implementation of the ERAS protocol is a challenge, and this has led to slow adoption of ERAS in some settings (9).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…Specific to urologists, overprescription of post‐operative narcotics is common with 67% of patients having surplus opioids after urologic surgery (Bates, Laciak, Southwick, & Bishoff, 2011). Nevertheless, surgeons across many specialties ranging from general surgery, colorectal, thoracic, gynaecologic and urologic surgery have begun to make significant strides to standardise post‐operative pain management and reduce opioid prescriptions by developing opioid‐sparing enhanced recovery after surgery (ERAS) protocols (Hughes, Ventham, McNally, Harrison, & Wigmore, 2014; Ljungqvist, Scott, & Fearon, 2017; Rubinkiewicz, Witowski, Su, Major, & Pedziwiatr, 2019; Schwartz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%